Households' basic needs satisfaction during the Coronavirus disease 19 (COVID-19) pandemic in Burkina Faso - Ousmane Traoré; Omer S. Combary; Yasmina d.D. Zina (Elsevier, 2022)
The Coronavirus disease 19 (COVID-19) pandemic has profoundly affected economic and health systems around the world. This paper aims to assess household access to basic foods and health care and food security attainment during the COVID-19 pandemic in Burkina Faso. We use the COVID-19 High-Frequency Phone Survey 2020 panel data supported by the World Bank and conducted by Institut National de la Statistique et de la Démographie (INSD). The pooled multinomial logistic, the panel logistic, and the panel ordered logistic regressions are used to analyse the access to basic foods, the access to health care and the food security of the households, respectively. The results show that during COVID-19, female-headed households, poor households and farm households remain the most vulnerable in terms of access to basic foods, health services and food insecurity. Furthermore, the results indicate that households living outside the capital, particularly in the other urbans, experience fewer difficulties obtaining basic foods than those residing in the capital and are also unlikely to experience food insecurity. For more effective policy responses to the COVID-19 or similar shocks, the interventions should focus on household socioeconomic conditions and distinguish between urban and rural areas.